Influências da resolução de atividades STEM no processo de engajamento estudantil - Medeiros, Juliana Guarize (2023)
Student engagement has been an important aspect when studying teaching and learning processes, being closely linked to issues such as student performance and dropout rates (FREDRICKS; BLUMENFELD; PARIS, 2004). For Fredricks, Blumenfeld and Paris (2004) student engagement is about the relationship formed between the student and their school activities. Bearing in mind the importance of engagement for the educational process and in order to seek new ways to encourage it in schools, we seek to understand its interlocution with STEM Education, an approach that has been widely discussed and researched, which integrates Science, Technology, Engineering and Mathematics, in the search for student leadership and problem solving. Thus, the present study aims to understand whether STEM activities enable or somehow promote student engagement. This study emerges from the project submitted by the Grupo de Estudos do Movimento STEM (GEMS) group and approved by the Fundação de Amparo à Pesquisa do Estado do Rio Grande do Sul (FAPERGS) in the public notice SEBRAE/RS 03/2021, entitled Jornada STEM - RS: Innovative Challenges in the School Context, which was aimed at high school students and teachers from public schools in the state of Rio Grande do Sul. As a methodology for this research, a case study with a qualitative approach was used. Therefore, the research was developed in three stages: 1) State of the art of academic productions on the theme of this study; 2) semi-structured interview with tutors from the STEM Journey finalist teams; and 3) focus group with the finalist students of Jornada STEM. The results found referring to the analysis of the first stage of this study point to the recentness of the subject in Brazil, in addition to a small number of publications related to the subject. As for the results of the second stage, they demonstrate that, according to the professors, the students showed a strong engagement when it comes mainly to the affective and agency dimensions of student engagement, which is in line with what is expected from STEM activities, as they they seek student protagonism and the student as an agent of action, a fact that defines the agency dimension. Finally, regarding the third stage of the study, students expressed greater engagement in the affective dimension, which is in line with the perception reported by the tutors. It is concluded from these results that further studies on the subject are needed, in order to understand the possibilities that STEM Education can offer to engage students in the teaching-learning process.